Insurtech innovations and telematics as «drivers» of change in the insurance industry - A.Yu. Polchanov; K.O. Halatiuk (Економіка, управління та адміністрування)
Introduction. The article discusses aspects of the development of Insurtech and telematics in the insurance industry, as well as their impact on innovative practices and efficiency of insurance processes. Scientific works of domestic and foreign scientists, articles, journals, online platforms, publications on the official websites of insurance companies and other specialized websites on the problems of the development of Insurtech and telematics became the information base of the research. The methodological basis of the study was general scientific and special research methods, in particular: abstraction (focusing on the main characteristics of Insurtech and telematics, highlighting the key advantages and challenges of Insurtech for the Ukrainian market); analysis (detailed study of all components of the subjects of analysis); comparison and analogy (study of examples of the use of modern technologies and telematics in the insurance industry).